2018
DOI: 10.2486/indhealth.2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s sleep quality: linked to social job characteristics?

Abstract: Besides dealing with high workload, being a teacher is challenging with respect to the social context. There is increasing evidence that adverse social job characteristics challenge sleep quality. The current study tests whether restraint sleep quality (defined as worse sleep quality before than during vacation) is related to time-related job stressors, job resources, and social job characteristics. Forty-eight elementary school teachers (42% women) participated both during the last week before and the first w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
(75 reference statements)
3
26
0
1
Order By: Relevance
“…However, more research is necessary to investigate whether subjective factors such as social stressors remain important beyond (other) objective factors in predicting job insecurity on a daily level. Our findings about the role of co‐worker conflicts on a daily level of job insecurity are in line with prior research about the consequences that social stressors at work exert on employees’ mental and physical health and on their job attitudes (e.g., Bruk‐Lee & Spector, ; Chen & Spector, ; Dormann & Zapf, ; Harris, Harvey, & Kacmar, ; Hershcovis & Barling, ; Kessler et al, ; Kottwitz, Gerhardt, Pereira, Iseli, & Elfering, ; Meier, Semmer, & Spector, ; Otto & Mamatoglu, ; Pereira et al, ; Spector & Jex, ). Thus, in addition to previous results, the present study shows that job insecurity is yet another negative consequence of social stressors—or, more specifically, conflicts with co‐workers—in the workplace.…”
Section: Discussionsupporting
confidence: 89%
“…However, more research is necessary to investigate whether subjective factors such as social stressors remain important beyond (other) objective factors in predicting job insecurity on a daily level. Our findings about the role of co‐worker conflicts on a daily level of job insecurity are in line with prior research about the consequences that social stressors at work exert on employees’ mental and physical health and on their job attitudes (e.g., Bruk‐Lee & Spector, ; Chen & Spector, ; Dormann & Zapf, ; Harris, Harvey, & Kacmar, ; Hershcovis & Barling, ; Kessler et al, ; Kottwitz, Gerhardt, Pereira, Iseli, & Elfering, ; Meier, Semmer, & Spector, ; Otto & Mamatoglu, ; Pereira et al, ; Spector & Jex, ). Thus, in addition to previous results, the present study shows that job insecurity is yet another negative consequence of social stressors—or, more specifically, conflicts with co‐workers—in the workplace.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, although the level of social stressors from supervisors in this study was generally low, it seems to play a role in sleep quality of railway workers as well. This result confirms recent evidence from teachers underscoring the importance of social-related job characteristics for a good night's sleep (Kottwitz et al 2018). In line with the present finding, fair treatment by management was found to be relevant to sleep patterns: within a prospective cohort study (Hayashi et al 2017), low organisational justice was found to be a risk factor for sleep in the sense of insomnia onset, even after adjustment for lifestyle and work-related variables.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas, sleep disorders caused by chronic stress can contribute to the risk of occupational burnout. At the same time, it was found that increased physical activity and proper sleep hygiene ensure high quality of sleep and may buffer the adverse effects of occupational stress [23-25].…”
Section: Discussionmentioning
confidence: 99%